Outcome of fibrillary glomerulonephritis (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY: We assessed the long-term follow up of all the patients with fibrillary glomerulonephritis diagnosed since 1992 at our centre of reference for renal pathology in Basel. METHODS: We performed a retrospective surveillance study with mail questionnaire based follow-up of all patients with the diagnosis of fibrillary glomerulonephritis found in the database of the department of renal pathology in Basel from 1992 to 2007. The outcome was assessed in terms of endstage renal disease (ESRD), death, reduction of proteinuria and improvement of estimated glomerular filtration rate (eGFR). RESULTS: We obtained sufficient follow up data from 16 out of 20 identified patients. The mean follow up time was 35 months (1–115.1). Six patients died (37.5%), three without having ESRD. Six patients (37.5%) reached ESRD, five of them went on hemodialysis. Thirteen patients (81.3%) received an immunosuppressive therapy with steroids, five of them in combination with cyclophosphamide. The group without immunosuppressive therapy was too small to compare the two groups. In relation to the histological pattern membranous glomerulonephritis (MGN) had a better outcome as compared to the other histological patterns. CONCLUSIONS: FGN is a heterogeneous disease associated with significant risk of ESRD and mortality. The histological type of the glomerulonephritis may influence the course of the disease.